2023
DOI: 10.3832/ifor4196-015
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of the ecological niche of Moringa peregrina (Forssk.) Fiori with topoclimatic heterogeneity in southern Iran

Abstract: Heterogeneity can be studied for any dynamic or fixed environmental factors over time. However, determining the extent of heterogeneity occurrence in terms of habitat suitability, variability of dynamic and fixed factors, as well as landform role is an issue that has received less attention. This study aimed to investigate the distribution of Moringa peregrina at two climate change scenarios, to identify the Region of High Heterogenetic (ROHH) of the habitats in those scenarios and to ascertain the heterogenei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 47 publications
(57 reference statements)
0
1
0
Order By: Relevance
“…Investigating the impact of climate changes on the distribution of M . peregrina using climate variables indicated that the mean monthly temperature ranges had less fluctuation in climate change scenarios [ 46 ]. Thus, LST changes are different from predicting scenarios for climate changes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Investigating the impact of climate changes on the distribution of M . peregrina using climate variables indicated that the mean monthly temperature ranges had less fluctuation in climate change scenarios [ 46 ]. Thus, LST changes are different from predicting scenarios for climate changes.…”
Section: Discussionmentioning
confidence: 99%
“…Ensemble habitat suitability modeling for M . peregrina was conducted according to the literature [ 46 ]. Modeling was conducted using 61 presence points and 120 pseudo-absence points.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The eSDM was prepared in R 4.3.1 from the models of maximum entropy (MAXENT), classification tree analysis (CTA), multivariate adaptive regression splines (MARS), generalized linear model (GLM), generalized boosting models (GBM), generalized additive models (GAM), artificial neural networks (ANN), and random forests (RF) in SSDM package [ 54 ]. A total of 1000 pseudo absence points were created randomly across the entire study area [ 55 ]. 70% of the data were allocated to training and 30% to testing.…”
Section: Methodsmentioning
confidence: 99%